A highly selective fluorescent sensor for Ca2+ and Sr2+ based on diarylethene with a furan-carbohydrazide unit. Issue 27 (5th July 2019) - Liu, Hongling; Cui, Shiqiang; Shi, Fu; Pu, Shouzhi
Abstract: A fluorescent sensor based on diarylethene has been designed and synthesized. The sensor not only exhibited excellent photochromic properties, but also has distinguishing ability for Ca 2+ and Sr 2+ from other metal ions. Upon addition of Ca 2+ and Sr 2+, its emission intensity enhanced 27-fold and 24-fold respectively, accompanied by the emission peak shifted from 439 nm to 484 nm for Ca 2+, and to 479 nm for Sr 2+ . The 1:1 stoichiometry between the sensor and the two ions was confirmed by Job's plot and HRMS. The LOD for Ca 2+ and Sr 2+ was determined to be 9.4 × 10 −8 mol L −1 and 7.2 × 10 −8 mol L −1, respectively. Furthermore, the sensor was applied in the detection of Ca 2+ and Sr 2+ in practical samples successfully. Graphical abstract: A highly selective fluorescent sensor for Ca 2+ and Sr 2+ based on diarylethene has been synthesized. The sensor could be applied to detect Ca 2+ and Sr 2+ in practical samples with high accuracy.Image 1 Highlights: This study reports a novel diarylethene derivative with a furan-carbohydrazide unit for the first time. The derivative could be acted as a fluorescent sensor for Ca 2+ and Sr 2+ with high selectivity. The sensor could be applied to the detection of Ca 2+ and Sr 2+ in practical samples with high accuracy.